Rural household diversity in the Leliefontein District of the Northern Cape Province of South Africa - Van Rooyen, Cornelius Johannes (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Agricultural Economics))--University of Pretoria, 2006.